2019
DOI: 10.3889/oamjms.2019.032
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Meningiomas - Outcome Associated With Type of Resection, Recurrence, Karnofsky Performance Score, Mitotic Count

Abstract: BACKGROUND: Meningiomas are the type of central nervous system tumours, derived from the cells of the arachnoid membrane that are well constrained from surrounding tissues, mainly no infiltrating neoplasm with benign features. Meningiomas consist about 15-20% of all primary intracranial neoplasms. AIM: The evaluation of the outcome of the operatively treated meningiomas in relation with the Karnofsky performance score, survival, recurrence, type of the surgical excision, histological type, mitotic count … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…In contrast, quality of life and return to work have been extensively studied in cranial meningiomas [ 19 , 20 , 21 , 22 ]. After surgery, anxiety, depression, and fatigue are common [ 23 , 24 , 25 , 26 , 27 , 28 ]. In the long term, quality of life may also be negatively affected by tumor recurrence, which is unexpectedly high in cranial meningiomas but not in spinal meningiomas [ 12 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, quality of life and return to work have been extensively studied in cranial meningiomas [ 19 , 20 , 21 , 22 ]. After surgery, anxiety, depression, and fatigue are common [ 23 , 24 , 25 , 26 , 27 , 28 ]. In the long term, quality of life may also be negatively affected by tumor recurrence, which is unexpectedly high in cranial meningiomas but not in spinal meningiomas [ 12 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on return to work have indicated that 17–33% of the patients operated for cranial meningioma were unable to return to work [ 26 , 27 , 28 ]. A recent Swedish study on patterns of sick leave prior to surgery and return to work up to two years after surgery in patients with intracranial meningiomas, showed that 79.0% of the patients were working full time one year prior to surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Robert Sumkovski et al found that sex, age, Karnofsky score etc. have predictive value for recurrence of different types of meningiomas (107). Histological grading of meningiomas also affects its recurrence, and with the increase of pathological grading, the recurrence rate increases greatly.…”
Section: Prognosis and Recurrencementioning
confidence: 99%
“…Although there are exceptions, there is a consensus that surgical resection of the tumor is the first option in treating meningioma. Wide surgical resection, histopathological grading, patient age, tumor size, and localization can be counted as prognostic factors for survival of the disease [16][17][18][19][20][21][22]. Some studies indicate that the recurrence rate of parasagittal and falcine meningiomas is higher than others.…”
Section: Discussionmentioning
confidence: 99%